A Simplified Trans-Septal Puncture Technique using a Needle Free Approach for Cryoablation of Atrial Fibrillation - Graham, Adam J (J Atr Fibrillation, 2017)
BACKGROUND: Trans-septal puncture (TSP) is routinely performed during treatment of atrial fibrillation (AF) and other electrophysiology procedures. The purpose of this retrospective observational study was the analysis of a novel needle free technique employed to gain access to the left atrium (LA). METHODS: The SafeSept Needle Free guidewire was delivered, using no needle, to the interatrial septum via a standard cryoablation sheath and dilator under transoesophageal guidance. The wire was then advanced into the LA with position confirmed by fluoroscopy. All cases were performed under general anaeasthetic (GA). RESULTS: The novel procedure was performed in 43 patients (38 paroxysmal AF (88.4%) and 5 persistent AF (11.4%)) with 100% success rate in accessing the LA. The procedure times (51.70 ±18.18) and fluoroscopy times (2.75 ± 3.35) were recorded. There were no complications seen in the cohort. CONCLUSION: Using SafeSept Needle Free wire for TSP had a high success rate and resulted in no complications, with the potential to reduce procedure and fluoroscopy times.